A Fast Online Replanning Algorithm Based on Intensity Field Projection for Adaptive Radiotherapy - Liu, Xiaomeng; Liang, Yueqiang; Zhu, Jian; Yu, Gang; Yu, Yanyan; Cao, Qiang; Li, X. Allen; Li, Baosheng (Frontiers in Oncology, 2020)
Purpose: The purpose of this work was to propose an online replanning algorithm, named intensity field projection (IFP), that directly adjusts intensity distributions for each beam based on the deformation of structures. IFP can be implemented within a reasonably acceptable time frame. Methods and materials: The online replanning method is based on the gradient-based free form deformation (GFFD) algorithm, which we have previously proposed. The method involves the following steps: The planning computed tomography (CT) and cone-beam CT image are registered to generate a three-dimensional (3-D) deformation field. According to the 3-D deformation field, the registered image and a new delineation are generated. The two-dimensional (2-D) deformation field of ray intensity in each beam direction is determined based on the 3-D deformation field in the region of interest. The 2-D ray intensity distribution in the corresponding beam direction is deformed to generate a new 2-D ray intensity distribution. According to the new 2-D ray intensity distribution, corresponding multi-leaf collimator (MLC) and jaw motion data are generated. The feasibility and advantages of our method have been demonstrated in five lung cancer IMRT cases. Results: Substantial underdosing in the CTV is seen in the original and the repositioning plans. The average prescription dose coverage (V100%) and D95 for CTV were 100% and 60.3Gy for the IFP plans compared to 82.6%(P<0.01) and 44.0Gy(P<0.01) for original plans, 86.7%(P<0.01 ) and 58.5Gy(P<0.01 ) for repositioning plans. On average, the mean total lung doses were 12.2Gy for the IFP plan compared to the 12.4Gy (P<0.01) and 12.6Gy (P<0.01) for the original and the repositioning plans. The entire process of IFP can be completed within three minutes. Conclusions: We proposed an online replanning strategy for automatically correcting interfractional anatomy variations. The preliminary results indicate that the IFP method substantially increased planning speed for online adaptive replanning.